Network analysis of Iranian's health insurance ecosystem before and after the introduction of Universal Health Insurance law - Rohaneh Rahimisadegh; Somayeh Noori Hekmat; Mohammad Hossein Mehrolhassani; Mohammad Jafari Sirizi (BMC, 2023)
Abstract Introduction The policy-making process in health reform is challenging due to the complexity of organizations, overlapping roles, and diversity of responsibilities. The present study aims to investigate and analyze the network of actors in the Iran health insurance ecosystem regarding the laws before and after the adoption of the Universal Health Insurance (UHI). Methods The present study was done by sequential exploratory mixed method research, consisting of two distinct phases. During the qualitative phase, the actors and issues pertaining to the laws of the Iranian health insurance ecosystem from 1971 to 2021 were identified through a systematic search of the laws and regulations section of the Research Center of the Islamic Legislative Assembly website. Qualitative data was analyzed in three steps using directed content analysis. During the quantitative phase, in order to draw the communication network of the actors in Iran's health insurance ecosystem, the data related to the nodes and links of the networks was collected. The communication networks were drawn using Gephi software and the micro- and macro-indicators of network were calculated and analyzed. Results There were 245 laws and 510 articles identified in the field of health insurance in Iran from 1971 to 2021. Most of the legal comments were on financial matters and credit allocation, and the payment of premiums. The number of actors before and after the enactment of the UHI Law was 33 and 137, respectively. The Ministry of Health and Medical Education and the Iran Health Insurance Organization were found the two main actors in the network before and after the approval of this law. Conclusions Adopting a UHI Law and delegating various legal missions and tasks, often with support to the health insurance organization, have facilitated the achievement of the law objectives. However, it has created a poor governance system and a network of actors with low coherence. Based on the results of the study, it is suggested to reduce actor roles and separate them for better governance and to prevent corruption in health insurance ecosystem. Introducing knowledge and technology brokers can be effective in strengthening governance and filling the structural gaps between actors.